Evaluation of Insecticides against Pest Complex of Cashew - Patel, R. B.; Patel, D. R.; Makati, J. P.; Patel, R. R. (International Journal of Economic Plants, 2018)
The investigation was carried out at the Agricultural experimental station, NAU, Paria (Gujarat, India) during 2009–10 to 2011–12. Total of eight treatments including control (unsprayed) were replicated thrice in randomized block design. Three sprays were carried out respectively at flushing, flowering and fruiting stages of cashew trees with the use of foot sprayer. Among all tested insecticides, lambda-cyhalothrin 5 EC @ 0.003% recorded lowest incidence of cashew pest complex viz. tea mosquito bugs, Helopeltis antonii Sign., leaf minor, Acrocercops syngramma, inflorence webber, Lamida moncusalis and apple and nut borers Thylocoptila panrosema i.e. 0.82, 13.64, 12.77, 12.64 and 12.85 %, respectively and recorded the highest raw nut yield of 860 kg ha-1 and it was at par with acetamiprid 20 SP @ 0.004%.